Characterization and Optimization of a Single-Transistor Active Pixel Image Sensor with Floating Junction Connected to Floating Gate. (21st May 2015) - Liu, Xin-Yan; Wu, Jun; Liu, Xiao-Yong; Zhang, Shuai; Lin, Xi; Zhang, Chun-Min; Wang, Peng-Fei; Zhang, David Wei
Abstract : The application of semifloating gate transistor (SFGT) as the single-transistor active pixel image sensor (APS) is investigated in this paper. This single-transistor (1T) APS can realize the functions of the conventional 3T CMOS image sensor. The device operation mechanism, optimization methods, and transient behavior measurements will be discussed. Because the floating junction of this device is connected to the floating gate, special behaviors such as floating gate voltage pinning effects were observed. The transient time measurement emulating the exposure procedure also confirmed the light sensing function as a single-transistor image sensor.